A novel conductive carbon-based forward osmosis membrane for dye wastewater treatment. (December 2022) - Wu, Lei; Li, Qianqian; Ma, Cong; Li, Ming; Yu, Yujuan
Abstract: Forward osmosis (FO) membrane fouling is one of the main reasons that hinder the further application of FO technology in the treatment of dye wastewater. To alleviate membrane fouling, a conductive coal carbon-based substrate and polydopamine nanoparticles (PDA NPs) interlayer composite FO membrane (CPFO) was prepared by interfacial polymerization (IP). CPFO-10 membrane prepared by depositing 10 mL of PDA NPs solution exhibited an optimum performance with water flux of 7.56 L/(m 2 h) for FO mode and 10.75 L/(m 2 h) for pressure retarded osmosis (PRO) mode, respectively. For rhodamine B and chrome black T dye wastewater treatment, the water flux losses were reduced by 21.6%, and 14.5% under the voltages of +1.5 V, and −1.5 V, respectively, compared with no voltage applied after the device was operated for 8 h. The applied voltage had little effect on the fouling mitigation performance of the CPFO membrane for neutral charged cresol red. After the device was operated for 4 cycles, the rejection rates of dyes wastewater treated by the CPFO membranes with applied voltage were close to 100%. The flux decline rate and flux recovery rate of CPFO membrane for rhodamine B and chrome black T wastewater treatment under application of +1.5 V and −1.5 V voltage after 4 cycles were 11.6%, 99.2%, and 16.7%, 98.9%, respectively. Therefore, the voltage-applied CPFO membrane still maintained good rejection and antifouling performance in long-term operation. This study provides a new insight into the preparation of conductive FO membranes for dye wastewater treatment and membrane fouling control. Highlights: Conductive coal-based forward osmosis (CPFO) membrane was fabricated. Three different charged dyes were investigated with positive and negative electric field. CPFO membranes showed superior anti-pollution performance with electric field. CPFO membranes applied voltage did not degrade during long-term operation.